Socio-Economic Status and Parental Savings for Higher Education among Malaysian Bumiputera Families - Zainal, Nor Rashidah; Kamaruddin, Rohana; Saiful Nathan, Siti Badariah (2009)
Socioeconomic status of a family is a benchmark for a student in Malaysia to get financial aid in education, on top of their academic performance. As the number of students obtaining good grades in their Sijil Pelajaran Malaysia examination increases, entry to public universities become more competitive and the chances to get a full education financing become smaller. Most students resort to loans provided by PTPTN as many still do not have any form of saving to finance their higher education. This study attempts to explore on parental saving for children’s higher education among Bumiputera across different socio-economic groups. A survey was conducted in UiTM and six of its affiliated colleges, with the total respondents of 371. Questionnaires to parents were distributed through the students. The results of the study reveal that only 15% of the students sampled received a form of financial aid from the government. The findings also show high correlation between the socio-economic status of parents and the level of awareness towards saving for their children. The findings are hoped to create awareness in the society that saving incentives for higher education can be utilized by all low and middle-income families in all communities.